Factores Resilientes en Tres Mujeres Maltratadas por su Pareja Que Consultaron El Cap (2015)
This research includes the description of resilient factors present in three women abused by their partner, and consulted the CAP whose objectives are aimed at identifying both the personal , cultural and psychosocial factors affecting the resilient process. The theoretical basis of the research is based on different concepts, actors, consequences and manifestations of resiliency factors with reference to authors such as Rutter, Kotliarenco, Vanistendael, and Grotberg among others. While the concept of domestic violence is addressed, as well as its different components.